Investigating the ferroelectric phases of sodium niobate: A computational approach - Alvarenga, Jesus A.M.; Laranjeira, José A.S. [UNESP]; Fabris, Guilherme S.L. [UNESP]; Sambrano, Julio R. [UNESP]; Moreira, Mario L.; Cava, Sergio S.; Ferrer, Mateus M. (Elsevier, 2025)
This study investigates the ferroelectric phases of NaNbO3 using density functional theory (DFT) simulations. Special attention is given to the antiferroelectric polymorph Pbcm and the purported polar phases with monoclinic P1m1 and orthorhombic P21ma symmetries. The results reveal similarities in the diffraction patterns and Raman spectra of the P1m1 and P21ma models, while the Pbcm model exhibits greater distinctiveness. A comprehensive mechanical analysis was conducted, revealing notable anisotropy in mechanical properties and an unusually negative Poisson's ratio for the R3c symmetry. In terms of ferroelectric properties, only the P1m1, P21ma, and R3c structures exhibit non-zero values for piezoelectric charge constants, indicating ferroelectric behavior. The Pbcm space group results from the stacking of two P21ma layers by a second-order improper rotation, explaining its antiferroelectric behavior. This work significantly contributes to the literature by providing a detailed understanding of the structural, vibrational, and mechanical properties of various NaNbO3 phases, highlighting the distinct ferroelectric and antiferroelectric behaviors.
Keywords: Ferroelectricity; Lead-free; Phase transitions; Piezoelectricity; Sodium niobate